PENGARUH FLEKSIBILITAS NOZZLE TERHADAP SISTEM PERPIPAAN - Budi Santoso; Hendra Prihatnadi (BATAN, 2010)
EFFECT OF NOZZLE FLEXIBILITY ON PIPING SYSTEMNOZZLE. Piping systems should be designed flexibly to avoid the burden more on the buffer tube and nozzle equipment. In conditions where space is limited then to create a routing that is flexible enough not impossible to achieve. As a result, the force generated would be enormous. One way to reduce the load more on the support and on the equipment nozzles with the method of nozzle fleksibility. In this method, the nozzle was not considered to be rigid but has a certain flexibility in accordance with the dimensions of the eaulpmen: Based on calculations using Caesar /I produced Fx=11926 kg, Fy =2510 kg, FZ=800 kg, Mx = -17712 kg-m, My =44514 kg-m and Mz =7813 kg-m. From these data there are still components that moment, that is My still quite large. To reduce the load on the nozzle so on nozzle factors included flexibility in order to get results Fx = 1989 kg, Fy =- 1938, FZ =1672, Mx = -1798 kg-m, My = 8106 kg-m and Mz = 3846 kg-m . Seeing the results of calculations with the nozzle flexibility and style of the moment turns out that there is less than the allowable limits so that this condition Is declared safe to Install. PENGARUH FLEKS/BILITAS NOZZLE TERHADAP S/STEM PERPIPAAN. Sistem perpipaan harus dirancang f1eksibel untuk menghindari beban lebih pada penyangga pipa maupun nozzle equipment. Pada kondisi dimana ruang sangat terbatas maka untuk membuat routing yang cukup fleksibel tidak mungkin dapat dicapai. Akibatnya gaya yang ditimbulkan akan sangat besar. Salah satu cara untuk mengurangi beban lebih pada penyangga maupun pada nozzle equipment yaitu dengan metode nozzle f1eksibilas. Dalam metoda inl nozzle tldak dianggap kaku tetapi memiliki fleksibllitas tetteniu sesual dengan dimensi darl equIpment. Berdasarkan perhitungan dengan menggunakan Caesar